Potential Use of Janus Kinase Inhibitors in the Treatment of Systemic Lupus Erythematosus - Huo R; Huang X; Yang Y; Lin J (Dove Medical Press, 2023)
Rongxiu Huo,* Xinxiang Huang,* Yang Yang, Jinying Lin Department of Rheumatology and Immunology, Guangxi Academy of Medical Sciences, the People's Hospital of Guangxi Zhuang Autonomous Region, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Jinying Lin, Department of Rheumatology and Immunology, Guangxi Academy of Medical Sciences, the People's Hospital of Guangxi Zhuang Autonomous Region, 6 Taoyuan Road, Qingxiu District, Nanning, Guangxi Zhuang Autonomous Region, 530016, People's Republic of China, Email jinyinglin@sina.comAbstract: Systemic lupus erythematosus (SLE) is a chronic, autoimmune disease with unclear pathogenesis. One characteristic of SLE is pro-inflammatory and anti-inflammatory cytokine imbalance. Janus kinase (JAK) is an intracellular non-receptor tyrosine kinase essential for many cytokine signaling pathways. Dysregulation of the JAK/signal transduction and transcriptional activator (STAT) pathway is an important process in SLE pathogenesis. Targeting JAK/STAT proteins can simultaneously block the functions of multiple cytokines. Current SLE treatment with non-specific corticosteroids and immunosuppressants can cause many adverse reactions. Therefore, treatments designed to control specific molecular targets for SLE are desirable. JAK inhibitors (JAKis) are a potential treatment for rheumatic diseases; however, the use of targeted signaling pathways to treat SLE remains a challenge, and its efficacy has not been determined. JAKis have shown positive results in reducing the use of glucocorticoids and/or non-specific immunosuppressants for SLE. JAKis are currently undergoing several clinical trials and expected to be the next stage in the treatment of SLE. Therefore, inhibition of the JAK/STAT pathway through JAKis may improve traditional treatment strategies for SLE.Keywords: systemic lupus erythematosus, Janus kinase, JAK/STAT pathway, JAK inhibitors